Scientific writing considerations: the title, abstract and keywords - Castro-Rodríguez, Yuri (2018)
The term scientific writing includes all standardized norms and protocols to achieve the adequate writing and diffusion of manuscripts in scientific journals. A scientific article’s first segments are usually the most read and depending on them the reader is encouraged to read the entire article. The proper wording of a title, abstract and key words allows the reader to understand and be interested in the research carried out. In addition, it simplifies the article’s search in databases and improves to more quickly diffusion. This scientific note summarizes the main recommendations and guidelines for the proper way to write a scientific article`s title, abstract and key words.